Utilization of Social Media in Building Social Customer Relationship Management in SMEs - Rodhiah, Rodhiah; Christinio, Elizabeth; Chrstianto, Einstein (International Journal of Social Science and Community Service, 2024)
Social media is growing rapidly and continuously. An organization with a social CRM system will build better relationships with customers, grow and gain trust and confidence... The activity partner is engaged in the business of creative handicraft products located in Serang, Banten province. In its activities, it faces problems, especially in terms of building social customer relationship management. PKM aims to assist partners in an effort to increase knowledge about Social Media Utilization in Building Social Customer Relationship Management. The activity method is carried out by training related to CRMS which is presented in the form of PPT including: understanding of social media, Social Media Strategy Versus SCRM, the main objectives of SCRM and so on. The training was conducted online with the assistance of 2 students. The results of the activity show that the provision of knowledge about social customer relationship management delivered in the form of PPT has been realized and is running smoothly. from the evaluation results the material has been understood well. Evidenced by the answers of partners who 100% can understand and understand the material presented.